ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN BIRO PERJALANAN WISATA PT. DWIDAYA TOUR - Prasetya, Wibawa (MAJALAH ILMIAH WIDYA, 2012)
Service is very important factor for Customer satisfaction which regareded as the key to success in maintaining the customer.The research on the service quality of Dwidaya Tour & Travel is based on 5 service quality dimensions: the tangible dimension, thereliability dimension, the responsiveness dimension, the assurance dimension and the empathy dimension. The methodology usedin this research is descriptive quantitative. The sample of the population is all 37 people as the Dwidayaâs active customers for thelast one year in November 2011 Comparing the service performance and customer importance, the satisfaction degree is 89, 13%,which means the customer has not really satisfied with Dwidayaâs service quality, and lowest satisfaction of customers derived fromthe services cape, with the satisfaction degree is 66,97%. The strategies suggested that can be implemented to boost the customersatisfaction towards for the company, is to maintain all the service aspects which have already seem to be satisfied the customersand emphasize all service aspects which havenât performed to satisfy the customers, especially the facility of Dwidaya.